A di-self-crosslinking hyaluronan-based hydrogel combined with type I collagen to construct a biomimetic injectable cartilage-filling scaffold. (15th July 2020) - Yao, Ya; Wang, Peilei; Li, Xing; Xu, Yang; Lu, Gonggong; Jiang, Qing; Sun, Yong; Fan, Yujiang; Zhang, Xingdong
Abstract: Injectable hydrogels have attracted increasing attention because of convenient clinical operation, non-invasive surgical procedure and seamless filling of irregular defects. Here, injectable di-self-crosslinking HSMSSA hydrogel was formed via fast thiol/maleimide click chemistry reaction and thiol oxidation reaction as primary and secondary self-crosslinking network, respectively. Molecular weight and precursor concentration significantly affected physichemical properties and biological functions of hydrogels. Although single HSMSSA gel (0.1 M Da, 10 mg/mL) had moderate injectability, preferable mechanical properties and good proliferative ability of chondrocytes in vitro, and could greatly promote cartilaginous tissue formation in vivo, the lack of adhesion sites resulted in an untenable situation in maintaining effective connections among newborn cell clusters. However, the biomimetic injectable di-self-crosslinking blend hydrogel by combing injectable HSMSSA and bioactive Col I had improved resistance to degradation, chondrocytes adhesion and proliferation, especially for multiples ascending genes expression level associated with hyaline cartilage formation and polyproteoglycan secretion, which might be a potential clinical treatment strategy for constructing injectable cartilage repair filler by combining expanded autologous chondrocytes. Statement of Significance: An injectable di-self-crosslinking Hyaluronan–Based hydrogel was formed via fast thiol/maleimide click chemistry reaction and thiol oxidation reaction as primary/secondary self-crosslinking network, respectively. Molecular weight and precursor concentration significantly affected physichemical properties and biological functions of the hydrogels. Although this HSMSSA gel (0.1 M Da, 10 mg/mL) had moderate injectability, preferable mechanical properties, and good proliferative ability of chondrocytes in vitro, and could greatly promote cartilaginous tissue formation in vivo, the lack of adhesion sites resulted in ineffective connections among newborn cell clusters. The biomimetic injectable di-self-crosslinking blend hydrogel improved chondrocyte adhesion and proliferation by combined injectable HSMSSA and bioactive Col I, especially for multiple ascending gene expression levels associated with hyaline cartilage formation and polyproteoglycan secretion. Graphical abstract: Image, graphical abstract